Духовна концепція сонетів Шекспіра - Габлевич, М. (Інститут літератури ім. Т.Г.Шевченка НАН України, 2009)
Предметом исследования в данной статье является особый символический образный язык сонетов В.Шекспира. Автор проектирует образный смысл Шекспировского сонетария на духовно-личную, межличностную, общественно-личную плоскости, обнаруживая возможности многоуровневого прочтения текста в пределах разных ассоциативных семантических полей и иллюстрируя тем самым тезис об универсальности гения Шекспира. Specific symbolic language of Shakespeare’s sonnets is under review in the article. The researcher projects the imagery contents of Shakespeare’s sonnets onto personal, interpersonal and social planes, which allows multilayer interpretation of the text in the framework of different associative semantic fields as well as substantiates the thesis about the universality of Shakespeare’s genius.